2022
DOI: 10.3343/alm.2022.42.6.638
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Expansion and Cytotoxicity Differ Depending on the Culture Medium Used

Abstract: Background: Adoptive cell therapy using umbilical cord blood (UCB)-derived allogeneic natural killer (NK) cells has shown encouraging results. However, because of the insufficient availability of NK cells and limited UCB volume, more effective culture methods are required. NK cell expansion and functionality are largely affected by the culture medium. While human serum is a major affecting component in culture media, the way it regulates NK cell functionality remains elusive. We elucidated the effects of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In particular, NK cell expansion and functionality are largely affected by the culture medium, and thus the effects of different culture media and human serum supplementation on CB-NK or P-NK cell expansion and functionality as well as relevant cellular vitality (e.g., high dose of cytokine stimulation for activation-induced cell death) are also of great importance. For instance, Moseman and Koh reported the variations in the expansion and cytotoxicity of NK cells due to the culture medium used between the serum-free and serum-containing media formulations, respectively [ 32 , 33 ]. Simultaneously, Shah et al reported the artificial antigen presenting cell (aAPC)-mediated log-scale expansion of UC-NKs from both fresh and cryopreserved CB units with anti-myeloma activity [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, NK cell expansion and functionality are largely affected by the culture medium, and thus the effects of different culture media and human serum supplementation on CB-NK or P-NK cell expansion and functionality as well as relevant cellular vitality (e.g., high dose of cytokine stimulation for activation-induced cell death) are also of great importance. For instance, Moseman and Koh reported the variations in the expansion and cytotoxicity of NK cells due to the culture medium used between the serum-free and serum-containing media formulations, respectively [ 32 , 33 ]. Simultaneously, Shah et al reported the artificial antigen presenting cell (aAPC)-mediated log-scale expansion of UC-NKs from both fresh and cryopreserved CB units with anti-myeloma activity [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expansion rate of NK cells is affected by various factors such as the source of NK cells, cytokines, feeder cells, media, and sample status (fresh vs. cryopreserved) [ 26 , 28 , 29 , 30 ]. Liu et al developed an adaptive NK cell expansion method using NK cells isolated from thawed PBMCs co-cultured with HLA-transfected 721.221 feeder cells in the presence of IL-15 (100 ng/mL), which led to a 2.4-fold increase after 14 days of culture [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have studied and developed effective protocols for the ex vivo expansion of NK cells from peripheral blood mononuclear cells (PBMCs) using both conventional K562 cells and genetically modified K562 cells expressing cofactor OX40L and cytokines mbIL-18 and -21 [ 22 , 23 , 24 , 25 ]. We also comparatively analyzed the effects that various culture media and supplements exerted on the expansion of NK cells obtained from cord blood samples [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, Natural killer (NK) cell activity is measured to assess innate or anti-tumor immunity and the effect of donor lymphocyte infusion and to diagnose hemophagocytic lymphohistiocytosis [1][2][3][4][5][6]. Flow cytometry is widely used to measure NK cell activity owing to its simplicity, reproducibility, and good correlation with the chromium release assay, which is the reference method [3,4].…”
mentioning
confidence: 99%